Clinical Accuracy of the G.LAB MD41A0 Upper Arm Blood Pressure Monitor in Pregnancy and Pre-Eclampsia Using the AAMI/ESH/ISO as Reference Standard - Zhang Y; Shi Z; Liang H; Chen M; Sun Y; Shang F; Wan Y (Vascular Health and Risk Management)
Ying Zhang,1,* Ziyun Shi,2,* Haixia Liang,1 Meixia Chen,1 Yan Sun,1 Fujun Shang,3 Yi Wan4 1Department of Obstetrics and Gynecology, Xijing 986 hospital, Fourth Military Medical University, Xi’an, Shaanxi, People’s Republic of China; 2Department of Obstetrics, Shaanxi Provincial People’s Hospital, Xi’an, Shaanxi, People’s Republic of China; 3Department of Cardiology, Xi’an Gem Flower Changqing Hospital, Xi’an, Shaanxi, People’s Republic of China; 4Department of Health Service, Fourth Military Medical University, Xi’an, Shaanxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi Wan, Department of Health Service, Fourth Military Medical University, No. 169 Changle Xilu, Xi’an, 710032, People’s Republic of China, Tel/Fax +86-29-84712676, Email wanyi@fmmu.edu.cn Fujun Shang, Department of Cardiology, Xi’an Gem Flower Changqing Hospital, Xi’an, Shaanxi, 710201, People’s Republic of China, Tel/Fax +86-29-86022756, Email shangfujun4@163.comObjective: Validation of blood pressure (BP) monitors in pregnant women are needed to ensure the accurate measurement of BP in pregnancy. Therefore the study aimed to evaluate the measurement accuracy of the G.LAB MD41A0 oscillometric automatic upper-arm blood pressure monitor in pregnancy and pre-eclampsia women according to the AAMI/ESH/ISO Universal Standard (ISO 81060– 2:2018).Methods: A total of 45 pregnant women were included in the cross-sectional validation study. The same left-arm sequential method was used for blood pressure measurement, and the blood pressure differences between the test device and the mercury standard reference were assessed according to the AAMI/ESH/ISO Universal Standard.Results: The participants included 15 normotensives, 15 gestational hypertension and 15 pre-eclampsia. The average (mean ± SD) differences between the device and mercury standard was − 0.84± 3.88 mmHg and − 0.58± 3.35 mmHg for systolic and diastolic blood pressure, respectively, for the validation Criterion 1. The SD of the averaged differences between the device and reference readings per participant was 2.92 mmHg and 2.28 mmHg for systolic and diastolic blood pressure, respectively, for the Criterion 2 of the universal standard.Conclusion: The G.LAB MD41A0 automatic upper-arm blood pressure monitor fulfills the criteria of the AAMI/ESH/ISO Universal Standard and can be recommended for clinical use and self-measurement in pregnancy and pre-eclampsia.Keywords: blood pressure monitor, validation, universal standard, pregnancy, pre-eclampsia